# SOLUTION: 10x³-51x²+54x

Algebra ->  Algebra  -> Test  -> Lessons -> SOLUTION: 10x³-51x²+54x      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help!

 Test Calculators and Practice Answers archive Word Problems Lessons In Depth

Question 375129: 10x³-51x²+54x
Found 2 solutions by jim_thompson5910, Earlsdon:
Answer by jim_thompson5910(28717)   (Show Source):
You can put this solution on YOUR website!
I'm assuming you want to factor.

Start with the given expression.

Factor out the GCF .

Now let's try to factor the inner expression

---------------------------------------------------------------

Looking at the expression , we can see that the first coefficient is , the second coefficient is , and the last term is .

Now multiply the first coefficient by the last term to get .

Now the question is: what two whole numbers multiply to (the previous product) and add to the second coefficient ?

To find these two numbers, we need to list all of the factors of (the previous product).

Factors of :
1,2,3,4,5,6,9,10,12,15,18,20,27,30,36,45,54,60,90,108,135,180,270,540
-1,-2,-3,-4,-5,-6,-9,-10,-12,-15,-18,-20,-27,-30,-36,-45,-54,-60,-90,-108,-135,-180,-270,-540

Note: list the negative of each factor. This will allow us to find all possible combinations.

These factors pair up and multiply to .
1*540 = 540
2*270 = 540
3*180 = 540
4*135 = 540
5*108 = 540
6*90 = 540
9*60 = 540
10*54 = 540
12*45 = 540
15*36 = 540
18*30 = 540
20*27 = 540
(-1)*(-540) = 540
(-2)*(-270) = 540
(-3)*(-180) = 540
(-4)*(-135) = 540
(-5)*(-108) = 540
(-6)*(-90) = 540
(-9)*(-60) = 540
(-10)*(-54) = 540
(-12)*(-45) = 540
(-15)*(-36) = 540
(-18)*(-30) = 540
(-20)*(-27) = 540

Now let's add up each pair of factors to see if one pair adds to the middle coefficient :

First NumberSecond NumberSum
15401+540=541
22702+270=272
31803+180=183
41354+135=139
51085+108=113
6906+90=96
9609+60=69
105410+54=64
124512+45=57
153615+36=51
183018+30=48
202720+27=47
-1-540-1+(-540)=-541
-2-270-2+(-270)=-272
-3-180-3+(-180)=-183
-4-135-4+(-135)=-139
-5-108-5+(-108)=-113
-6-90-6+(-90)=-96
-9-60-9+(-60)=-69
-10-54-10+(-54)=-64
-12-45-12+(-45)=-57
-15-36-15+(-36)=-51
-18-30-18+(-30)=-48
-20-27-20+(-27)=-47

From the table, we can see that the two numbers and add to (the middle coefficient).

So the two numbers and both multiply to and add to

Now replace the middle term with . Remember, and add to . So this shows us that .

Replace the second term with .

Group the terms into two pairs.

Factor out the GCF from the first group.

Factor out from the second group. The goal of this step is to make the terms in the second parenthesis equal to the terms in the first parenthesis.

Combine like terms. Or factor out the common term

--------------------------------------------------

So then factors further to

===============================================================

Answer:

So completely factors to .

In other words, .

Note: you can check the answer by expanding to get or by graphing the original expression and the answer (the two graphs should be identical).

If you need more help, email me at jim_thompson5910@hotmail.com

Also, feel free to check out my tutoring website

Jim

Answer by Earlsdon(6294)   (Show Source):
You can put this solution on YOUR website!
First factor an x.
Now factor the trinomial.